Effects of organic and inorganic copper on cecal microbiota and short-chain fatty acids in growing rabbits - Du, Yanan; Tu, Yun; Zhou, Zeyang; Hong, Rui; Yan, Jiayou; Zhang, Gong-Wei (Frontiers in Veterinary Science, 2023)
Introduction Copper (Cu) is an essential trace element for the growth of rabbits. This study aimed to investigate the effects of different Cu sources on intestinal microorganisms and short-chain fatty acids (SCFAs) in growing rabbits. Methods The experimental animals were randomly divided into four experimental groups, each group comprised eight replicates, with six rabbits (half male and half female) per replicate. And they were fed diets was composed by mixing the basal diet with 20 mg/kg Cu from one of the two inorganic Cu (cupric sulfate and dicopper chloride trihydroxide) or two organic Cu (cupric citrate and copper glycinate). Cecal contents of four rabbits were collected from four experimental groups for 16S rDNA gene amplification sequencing and gas chromatography analysis. Results Our results indicate that the organic Cu groups were less variable than the inorganic Cu groups. Compared with the inorganic Cu groups, the CuCit group had a significantly higher relative abundance of Rikenella Tissierella, Lachnospiraceae_NK3A20_group, Enterococcus, and Paeniclostridium, while the relative abundance of Novosphingobium and Ruminococcus were significantly lower (p < 0.05). The SCFAs level decreased in the organic Cu groups than in the inorganic Cu groups. Among the SCFAs, the butyric acid level significantly decreased in the CuCit group than in the CuSO4 and CuCl2 groups. The relative abundance of Rikenella and Turicibacter genera was significantly negatively correlated with the butyric acid level in the CuCit group compared with both inorganic Cu groups. These results revealed that the organic Cu (CuCit) group had an increased abundance of Rikenella, Enterococcus, Lachnospiraceae_NK3A20_group, and Turicibacter genera in the rabbit cecum. Discussion In summary, this study found that organic Cu and inorganic Cu sources had different effects on cecal microbiota composition and SCFAs in rabbits. The CuCit group had the unique higher relative abundance of genera Rikenella and Lachnospiraceae_NK3A20_group, which might be beneficial to the lower incidence of diarrhea in rabbits.